Distributed leadership for personalized learning. Issue 3 (2nd July 2020) - Kallio, Julie M.; Halverson, Richard
Abstract: Personalized learning refers to a collection of practices designed to place student interests and needs at the heart of schooling. Schools that implement personalized learning need leaders that support educators and students in redesigning the core practices of teaching and learning in K-12 schools. To answer the question of how leaders support this redesign, we use distributed leadership theory to focus on the macrotasks and microtasks that leaders enact to create the conditions for personalized learning practices. Drawing on a five-year, qualitative study of 11 personalized learning programs in the Midwest, we identify three macrotasks supporting personalized learning: reorganizing learning environments to support student voice and choice, assembling idiosyncratic technology ecosystems to distribute teaching and learning tasks, and redesigning instructional time to prioritize student's interests, agency, and learning relationships. After we describe a number of microtasks associated with each macrotask, we discuss how a consideration of these kinds of leadership tasks can open the contemporary discussion of personalized learning from a narrow focus on learning technologies to an expansive vision of student-centered school reform.